A Case of Pyelonephritis With Bacteremia Caused by Gardnerella Vaginalis in a Man. Issue 6 (November 2018) - Pritchard, Haley
Abstract : Abstract: Gardnerella vaginalis is known to be associated with bacterial vaginosis and has less frequently been reported to contribute to polymicrobial gynecologic and postsurgical infections in women. It is not considered to be a common cause of disease in men. We now report a case of pyelonephritis with G. vaginalis bacteremia in a male patient with nephrolithiasis. We found 10 other cases of Gardnerella infection in men and reviewed the predisposing factors, case descriptions, treatments, and outcomes. Infection due to G. vaginalis in men is rare, but it should be considered to be a potential pathogen men, especially in those with urogenital tract abnormalities. Abstract : Gardnerella vaginalis is associated with bacterial vaginosis and polymicrobial extra-vaginal infections in women, but is a very uncommon pathogen in men. The authors report a male patient with pyelonephritis and bacteremia due to Gardnerella . They also review the case summaries and outcomes of previously reported cases of Gardnerella infections in male patients. Gardnerella infections in men are rare but should be considered in men with urogenital abnormalities.